Apparent permeability of organic matter in shale considering pore size distribution. (2nd February 2023) - Tian, Yuanyuan; Yan, Changhui; Deng, Hucheng; Chen, Qing; He, Yanqing; Feng, Xiaolong; Li, Kai
Highlights: Apparent permeability model coupled pore size distribution of organic matter in shale is built. The influence factors of Kapp are clarified as dominant pore diameter, frequency of the dominant pore diameter and porosity. When P≥10Mpa, the Gaussian and log-normal PSD models are valid to estimate Kapp . Abstract: The gas flow in shale nanopores is a crucial factor for shale gas exploitation. Organic matter in shale is an important constituent of gas shale reservoirs because of its gas storage ability. Current apparent permeability ( K app ) models focus on permeability calculations derived from pores with a given diameter or given mathematical distribution instead of pore size distribution. We confirmed the gas mass flux in organic matter by modifying the molecular diffusion coefficient and adsorption amount related to surface diffusion and flow regime transformation critical conditions such as pore size and pressure. Then, K app was calculated by coupling the mass flux with the pore size distribution. Our research shows that steps occur in the K app curves of organic matter owing to the flow regime transformation from transition flow to slip flow. Additionally, porosity, dominant pore diameter and frequency were the main factors affecting the K app of organic matter.